2019
DOI: 10.1111/1756-185x.13572
|View full text |Cite
|
Sign up to set email alerts
|

Work disability in a multi‐ethnic Malaysian systemic lupus erythematosus cohort: A cross‐sectional study

Abstract: Aim To determine the prevalence of work disability (WD) among patients with systemic lupus erythematosus (SLE) and its associated factors. Method This was a cross‐sectional study involving SLE patients aged 18‐56 years from Universiti Kebangsaan Malaysia Medical Centre (UKMMC). Employment history was obtained from clinical interviews. WD was defined as unemployment, interruption of employment or premature cessation of employment due to SLE at any time after the diagnosis. SLE disease characteristics, presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…25 Interestingly, a similar rate (44%) of cSLE patients with no paid job has been described in the Dutch population, a high-income country. 26 High rates of unemployment were also described in SLE patients from Germany (49%) 27 and Malaysia (22%), 28 and a job loss rate of 49% was reported after an average disease duration of 13 years in the United States. 29…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Interestingly, a similar rate (44%) of cSLE patients with no paid job has been described in the Dutch population, a high-income country. 26 High rates of unemployment were also described in SLE patients from Germany (49%) 27 and Malaysia (22%), 28 and a job loss rate of 49% was reported after an average disease duration of 13 years in the United States. 29…”
Section: Discussionmentioning
confidence: 99%
“…25 Interestingly, a similar rate (44%) of cSLE patients with no paid job has been described in the Dutch population, a high-income country. 26 High rates of unemployment were also described in SLE patients from Germany (49%) 27 and Malaysia (22%), 28 and a job loss rate of 49% was reported after an average disease duration of 13 years in the United States. 29 However, in our study, most of the unemployed subjects reported that have never worked before due to limitation caused by disease flares or organ damage, such as fatigue, pain, movement restriction, hemodialysis, and frequent medical appointments.…”
Section: Discussionmentioning
confidence: 99%
“…Email: drwongsa@gmail.com All of circumstances might be involved by health and sick leave 12 . As same as diabetes [13][14][15] , cardiovascular disease 14,16 , cancer 14,17 , obesity 14 , back or neck pain 14,18 , Systemic Lupus Erythematosus (SLE) 19 , mental health problems and chronic pain 20 were considered as prolong illness among them. Moreover, work disability in patients with SLE was associated in particular higher disease activity, presence of renal involvement and organ damage 19 .…”
Section: Corresponding Author: Wongsa Laohasiriwongmentioning
confidence: 99%
“…As same as diabetes [13][14][15] , cardiovascular disease 14,16 , cancer 14,17 , obesity 14 , back or neck pain 14,18 , Systemic Lupus Erythematosus (SLE) 19 , mental health problems and chronic pain 20 were considered as prolong illness among them. Moreover, work disability in patients with SLE was associated in particular higher disease activity, presence of renal involvement and organ damage 19 . Previous studies reported factors associated with absence to work or disability were working hours, working place away from home, no autonomy in planning task as well as fatigue during working was one of the risk of sickness that lead to absence from wok or work disability 21 .…”
Section: Corresponding Author: Wongsa Laohasiriwongmentioning
confidence: 99%
“…How many of these elements contribute to any one individuals’ work status will vary across the life of the individual as well as where (and when) they live. The study by Abu Baker et al contributes to our knowledge in this area by examining the experience of a cohort of Malaysian patients with systemic lupus erythematosus. This is quite a specific population to study, and yet given the variables involved in determining work disability, it is important for Malaysia to understand what is happening in their own population and socio‐political environment.…”
mentioning
confidence: 99%